Agreement morphemes in Northern Sotho constructions : a morphological and semantic study - Kganakga, Thobakgale Johannes (My University, 2004)
Refer to document
Thesis (M. A. (African Languages)) -- University of Limpopo, 2004
Keywords: Northern Sotho Language; Morphology; Grammar, Comparative and general -- Morphology; Northern Sotho language -- Grammar; Grammar, Comparative and general -- Agreement